STUDI PERBAIKAN FORMULASI DYESTUFF PADA MIXING COLOR SEBAGAI ALTERNATIF PERBAIKAN KERATAAN WARNA PADA PEWARNAAN DASAR (DYEING) KULIT DOMBA GREEN CABRETTA - Helis Rianti; Elis Nurbalia; Prasetyo Hermawan (Politeknik ATK Yogyakarta, 2020)
The aim of this study was to find a solution to the problem of the dyeing process of Sheep Cabretta Glove skin that experiences uneven color. One of the causes of uneven color is based on the use of different types of dyestuffs. In changing the formulation of dyeing, the focus is on replacing similar dyestuffs with acid dyes or metal complex dyes. The expected result is that the mixing of the two colors will be more optimal and the color on the skin is evenly distributed. The factors that influence the basic coloring process are pH, temperature, time, and IEP (Iso Electric Point). The raw material used is quality I - IV / V TBL of sheep crust, with shaving thickness of 0.5 - 0.55 mm, and the number of 5 sheets or 16.54 sqft with a weight of 1200 gr. While the auxiliary materials used in the dyeing processed are , Inoderme Green CJR (metal complex dyes), Coriacide Yellow 3JN (acid dyes), Ammonia, Synectan LB. The stages of the processed carried out are wetting back, retanning, fixation, dyeing, fatliquoring, shaving, and Top Fat. The method used are of observation, interviews, direct work practice, and literature study. The dyeing process method used for making sheep Cabretta glove articles is a through dyeing method. The expected results are uniform color leather by mixing similar dyestuffs, namely acid dyes or metal complex dyes and the skin obtained is green, according to organoleptic views it is not in accordance with customer standards, So that a literature study was carried out to change the dye formulation by using acid dyes, namely Coriacide Yellow 3JN with Coriacide Green BS or Coriacide Dark Green JT dyes and metal complex dyes namely Inoderme Green CJR with Inoderm Yellow JS or Melioderm HF Yellow R dyes which are expected to increase the uniform of color on the skin surface.